German-Chinese trade relations: How dependent is the German economy on China? - Andreas Baur; Lisandra Flach (CESifo GmbH, 2022)
In recent decades, China has risen to become Germany's most important trading partner for international trade in goods. Has Germany become too dependent from trade with China? An analysis using direct and indirect value-added linkages along the supply chain shows that China plays an important, but by no means dominant role for Germany as a supplier or destination market. However, in a survey conducted by the ifo Institute, 46% of German firms in the manufacturing sector state that they currently depend on important intermediate inputs from China. Of those, almost half of the firms are planning to reduce imports from China in the future. The most frequently mentioned reasons for reducing imports from China are the desire to decrease dependencies and increase diversification, increased freight costs and disruptions in transportation, as well as political uncertainty. An analysis at the product level shows that the German economy depends on several critical industrial goods and raw materials from China.
Keywords: 330